Gastrodiae Rhizoma Water Extract Ameliorates Hypothalamic–Pituitary–Adrenal Axis Hyperactivity and Inflammation Induced by Chronic Unpredictable Mild Stress in Rats - Wang, Min (Biomed Res Int, 2020)
Gastrodiae Rhizoma is a highly valuable traditional herbal medicine commonly used to treat neurological disorders. The present study is designed to determine the antidepressant-like effect of the Gastrodiae Rhizoma water extract (GRWE) on a depression model and the potential mechanisms. The chronic unpredictable mild stress (CUMS) rat model was used to induce depression. The sucrose preference test, open field test, forced swimming test, and tail suspension test were performed to assess the depressive-like behaviors, respectively. Hypothalamic–pituitary–adrenal (HPA) function was measured via plasma corticosterone (CORT), adrenocorticotrophic hormone (ACTH), hypothalamic corticotropin-releasing factor (CRF), and glucocorticoid receptor (GR) concentrations. Plasma concentrations of proinflammatory cytokines including interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) were also evaluated. The results showed that GRWE significantly attenuates the behavioral abnormalities in CUMS rats, as shown by elevated sucrose consumption, raised locomotor activity, and reduced immobility duration. Moreover, GRWE treatment reduced CORT, ACTH, CRF, and GR levels and decreased the plasma IL-1β, IL-6, and TNF-α concentrations. These findings indicate that GRWE improves depressive behaviors in a chronic stress model of rats; its effect may be ascribed to the modulation of the HPA axis activity and inflammatory response.